ANALYSIS OF SUBJECTIVE INDICATORS OF QUALITY OF LIFE IN MAKURDI TOWN OF BENUE STATE, NIGERIA - D. Mngutyo, Arc. Irene; DAM, Daniel Peverga (IJRDO - Journal of Social Science and Humanities Research, 2018)
Quality of life measurements are an appropriate means for achieving an understanding of Human needs. This study analyses the quality of life in Makurdi town of Benue state, Nigeria using subjective indices. A sample of 400 respondents was determined based on Taro Yamane formula; and questionnaires were administered on them. The data collected was analysed using descriptive statistics. The result of the study shows that demographically, males and people within the age group of 31-40years and educated people dominated the study area. The result of the study shows that only 1% of the respondents are currently on top of the ladder of quality of life, enjoying the best possible life in the study area. About 74% of the respondent occupied step 5 below. This implies that majority of the people in the study area are currently far from desired quality of life. The study also reveals that in the next five years, about 47% of the people hope to be between steps 6-10 on the quality of life ladder in the study area. This shows an increase of 21% when compare with the current situation in the same range. However, the best possible quality of life in the next five years will remain constant with only 1%. The study reveals that the general well-being of people in Makurdi town on the basis of their experiences of positive, good, pleasant, happiness, joyfulness and contentment is low hence majority of the people have no such experiences but rather the opposite which include negative, bad, unpleasant, sad, angry and discontent. It therefore means that majority of the residents of Makurdi town are in the lower levels on the ladder of quality of life. This study recommends deliberate effort by government and NGOs to provide the basic social amenities and social security packages that will improve people’s quality of life in the town.